Hubungan Pemberian ASI Eksklusif dan Pengetahuan Ibu dengan Kejadian Stunting di Wilayah Puskesmas Cot Seumeureung - Aulia, Febi; Rinawati, Rinawati; Marniati, Marniati; Harahap, Laila Apriani Hasanah (Polyscopia, 2024)
Stunting is a serious health issue that impedes optimal child growth, particularly due to inadequate height for age. This study aims to examine the relationship between exclusive breastfeeding and maternal knowledge levels with stunting prevalence in the Cot Seumeureung Public Health Center region, Aceh Barat. Employing a cross-sectional research design, the study involved 95 toddlers selected through proportional random sampling. Data were analyzed using Chi-Square statistical tests to determine associations between the variables under study. Results indicate a significant correlation between exclusive breastfeeding and stunting prevalence (p=0.002), as well as between maternal knowledge and stunting incidence (p=0.001). The findings highlight that exclusive breastfeeding and maternal knowledge are critical factors in stunting prevention, underscoring the importance of enhanced breastfeeding education for mothers as a preventive measure.